Biosynthesis and Functionalization of Bacterial Cellulose Membranes with Cerium Nitrate and Silver Nanoparticles - Teixeira,Stéfani Regina Zibetti (2019)
This work aimed to synthesize bacterial cellulose (BC) membranes functionalized with Ce(NO3)3 and silver nanoparticles (AgNPs) heat-treated in oven and autoclave. The AgNPs were characterized by TEM and the membranes were characterized by their rehydration capacity, Thermogravimetric Analysis (TGA), Scanning Electron Microscopy with Dispersive Energy Spectroscopy (SEM/EDS), Wide-angle X-ray Diffractometry (XRD), Atomic Absorption Spectroscopy (AAS), antimicrobial activity and cytotoxicity. The BC membranes were white to light yellow or brown indicating functionalization with AgNps with 20 nm. XRD detected a decrease in the degree of crystallinity in functionalized membranes. The autoclaved samples exhibited the largest porosity and good rehydration capacity. AAS showed Ag presence in all samples. The best antibacterial activity was achieved for the membrane’s oven treated with 40 ppm of AgNPs. Among the functionalized membranes, the most recommended to be used as burn dressing is the Ag40A and Ag20CN1.1A since they showed good porosity, good antimicrobial activity, and better suitable cell viability.